The Influence of Self-Regulation on Early Childhood Education Teachers' Readiness for Curriculum Change in Indonesia - Putri, Nilamsari Kusumawati; Pranoto, Yuli Kurniawati Sugiyo; Nuzulia, Siti (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2024)
The challenges of implementing new curricula, such as insufficient infrastructure, high parental expectations, and varying levels of teacher quality, have left many early childhood education (PAUD) teachers unprepared for curriculum changes. Teachers often face difficulties adapting to new instructional materials, revising learning plans, updating teaching processes, and aligning assessments with curriculum requirements. Curriculum transitions are a global phenomenon, posing challenges for educators in various contexts. This study explores the influence of self-regulation on PAUD teachers' readiness for curriculum change in Indonesia. Using a quantitative approach with simple linear regression analysis, data were collected from 113 teachers selected through quota sampling based on calculations using the G*Power software (α = 0.05, power = 0.95, effect size f = 0.15). Validated instruments assessed self-regulation and readiness for curriculum change, ensuring cultural and linguistic relevance. Results from SPSS analysis demonstrated a significant positive relationship (p = 0.001, CI: 1.031–1.934) between self-regulation and readiness for curriculum change. Teachers with higher self-regulation exhibited greater adaptability and competence in meeting the demands of curriculum updates. This study highlights the pivotal role of self-regulation in enhancing teacher readiness, enabling educators to address challenges, develop new skills, and align their practices with curriculum requirements. The findings underscore the need for professional development programs to foster self-regulation and institutional support to facilitate smooth transitions during curriculum reforms. Future research should adopt longitudinal designs to explore the dynamic processes of teacher readiness over time and across diverse educational settings.